2013
DOI: 10.1016/j.apenergy.2012.11.030
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopy study of gasoline partially premixed compression ignition spark assisted combustion

Abstract: ElsevierPastor Soriano, JV.; García Oliver, JM.; García Martínez, A.; Mico Reche, C.; Durret, R. (2013). A spectroscopy study of gasoline partially premixed compression ignition spark assisted combustion. Applied Energy. 104:568-575. doi:10.1016Energy. 104:568-575. doi:10. /j.apenergy.2012. and increases efficiency. However these combustion concepts have some drawbacks, related to 24 combustion phasing control, which must be overcome. In this way, the use of a spark plug has shown 25 to be a good solution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…However, the concept demonstrated difficulties at low load conditions using gasoline with octane number (ON) greater than 90 [15] [16]. In this sense, the spark assistance provided temporal and spatial control over the gasoline PPC combustion process [17][18] [19], but resulted in unacceptable NOx and soot emissions [20], even using double injection strategies [21] [22].…”
Section: Homogeneous Charge Compression Ignition (Hcci) a Widely Invmentioning
confidence: 99%
“…However, the concept demonstrated difficulties at low load conditions using gasoline with octane number (ON) greater than 90 [15] [16]. In this sense, the spark assistance provided temporal and spatial control over the gasoline PPC combustion process [17][18] [19], but resulted in unacceptable NOx and soot emissions [20], even using double injection strategies [21] [22].…”
Section: Homogeneous Charge Compression Ignition (Hcci) a Widely Invmentioning
confidence: 99%
“…With the aim of improving the PPC cycle-to-cycle control at low loads using high ON gasolines, PPC spark assisted concept has been studied [12] [13]. It has been demonstrated that the spark assistance provides temporal and spatial control over the combustion process [14], however the high local reactivity required between the spark plug electrodes at the start of spark timing and the flame propagation process result in an unacceptable NOx and soot emissions [15].…”
Section: Introductionmentioning
confidence: 99%
“…In PCCI or PPCI derived from HCCI, the end point of fuel injection and the start point of combustion are separated for preferred control over the start of combustion and better fuel-air premixed state at the beginning of combustion [14]. References [15][16][17][18] conducted numerical simulation or experimental study on PPCI combustion.…”
Section: Introductionmentioning
confidence: 99%